Safety, immunogenicity and pregnancy outcomes in mothers and infants after vaccination with an adenovirus-vector COVID-19 vaccine during pregnancy - Aguilar, Gloria; Tapia-Calle, Gabriela; Robinson, Cynthia; Baron, Benoit; Lowson, David; Maximos, Bassem; Rezelj, Veronica V.; de Groot, Anne Marit; Bet, Nicole; van Paassen, Vitalija; Le Gars, Mathieu; Struyf, Frank; et al. (Human vaccines & immunotherapeutics, 2025)
COVID-19 during pregnancy can be associated with adverse pregnancy and infant outcomes. We assessed the safety, reactogenicity, and immunogenicity of maternal vaccination with Ad26.COV2.S COVID-19 vaccine and monitored serum and breast milk antibody levels in mothers and infants until 6 months post-delivery. This open-label Phase 2 study enrolled previously COVID-19 vaccinated or COVID-19-vaccine-naive healthy pregnant women in trimester two or three (NCT04765384). All women received a single dose of Ad26.COV2.S. Mothers and infants were followed-up for safety until 1-year post-partum and for immunogenicity, including antibodies in breast milk, until 6 months post-partum. Recruitment was stopped at 51 participants due to rapidity of roll-out of COVID-19 vaccines recommended during pregnancy. Ad26.COV2.S was well-tolerated regardless of previous COVID-19 vaccination history. All pregnancies resulted in a live infant, four were preterm. One serious adverse event of placental insufficiency Day-36 post-vaccination was considered vaccine-related by the investigator. One infant died due to complications associated with an unrelated ventricular septal defect. Ad26.COV2.S induced robust immune responses in women with different COVID-19 vaccination histories. Spike-binding antibody (SAbs) and virus neutralizing antibody (NAbs) titers at delivery tended to be higher in mothers vaccinated during trimester three. Maternal serum and cord blood were strongly correlated. 100% of infants had detectable SAbs at aged 6 months, and 70.6% had detectable NAbs, including 68.2% born to initially vaccine-naïve mothers. Maternal vaccination with an adenovirus-vector vaccine was well-tolerated and immunogenic in mothers and infants. These data could support the adoption of heterologous booster regimens during pregnancy and future adenovirus-vector vaccine development.